Право собственности: пределы и ограничения - Бергер, Яна (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the selected limitation of the right to property. The author is of the opinion that establishing the boundaries of property rights in the law system serves the interests of society and supports the economic, social, political and economic well-being.